Tuberculoso orchiepididymitus in insulinodependent Type 2 diabetes Mellitus: Case report: Orquiepididimitis tuberculosa en diabetes Mellitus Tipo 2 insulinodependiente: Reporte de caso - Carrillo-Sanabria, Gonzalo (2022)
Introduction: There is little information in Peru on the association of tuberculous orchiepididymitis in relation to immunosuppressed patients, being an endemic country of tuberculosis and there is an increase in the prevalence of chronic noncommunicable diseases such as diabetes, producing wrong diagnoses.  Clinical Case: We present the case of a 70-year-old man with a history of type 2 diabetes mellitus who was admitted to the outpatient clinic due to dysuria and frequency. On physical examination, a hard, non-painful right testicle, the ultrasound showed signs of epididymal abscess in the scrotal wall of the Right testicle, which is why an infected neoplasm is suspected, and a right orchiectomy is performed, later in the histological study, multinucleated Langhans-type giant cells with granulomatous areas suggestive of tuberculosis are shown, which is why it is proposed that in the presence of urological symptoms in immunosuppressed patients, it is ruled out tuberculosis.